Case report: Single-session double-Ilizarov lengthening technique in the treatment of a child with congenital fibular deficiency - Shu, Wen; Yue, Changjie; Zhong, Haobo; Tang, Xin (Frontiers in Pediatrics, 2022)
Background Congenital fibular deficiency is a rare disease with a broad spectrum of deformities. Associated anomalies complicate the symptoms of patients and, consequently, individualized treatments that aim at normal function and acceptable appearance. Case presentation We present a case of congenital femoral and fibular shortening in the right lower limb with foot anomaly at school age. The patient underwent limb lengthening procedure in a single session on the right femur and tibia at the same time using a double-Ilizarov frame. The functional and cosmetic of his right lower extremity achieved a good outcome. Complications were minimal except for the superficial infection. Treatment lasted for 9.2 months, allowing for returning the patient to functional activity as soon as possible. Conclusion A satisfactory result was obtained with limb lengthening in a single session using double Ilizarov external fixators in a school-aged patient with congenital fibular deficiency.